2014
DOI: 10.3171/2014.4.peds13451
|View full text |Cite
|
Sign up to set email alerts
|

Utility of computed tomography or magnetic resonance imaging evaluation of ventricular morphology in suspected cerebrospinal fluid shunt malfunction

Abstract: Object It is common to evaluate children with suspected CSF shunt malfunctions using CT of the head or, more recently, “quick brain” MRI. However, the reliability of using ventricular behavior, as assessed on cranial imaging during previous presentations with shunt obstructions, is not well defined. The authors conducted a study to determine if CT or MRI of ventricular morphology added useful clinical information in the evaluation of shunt malfunctions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…27 Pretest probabilities were estimated for a symptomatic, at-risk population. 2,6,7,28,29 Probability of shunt failure was found to be 30% based on a quality improvement study evaluating a pathway used by providers at a tertiary care pediatric ED with 85 000 patient visits per year, which is similar to our own institution. 2,30 To define the test characteristics of imaging modalities, we used a weighted average from published data that evaluated the test characteristics of the SS, CT, POCUS, and fsMRI.…”
Section: Clinical Inputsmentioning
confidence: 93%
“…27 Pretest probabilities were estimated for a symptomatic, at-risk population. 2,6,7,28,29 Probability of shunt failure was found to be 30% based on a quality improvement study evaluating a pathway used by providers at a tertiary care pediatric ED with 85 000 patient visits per year, which is similar to our own institution. 2,30 To define the test characteristics of imaging modalities, we used a weighted average from published data that evaluated the test characteristics of the SS, CT, POCUS, and fsMRI.…”
Section: Clinical Inputsmentioning
confidence: 93%
“…The neuropathological consequences of hydrocephalus could explain this finding. Deleterious effects of congenital hydrocephalus in pre-clinical animal models include altered myelination and cortical thinning in later development (Del Bigio, 2010; Juranek & Salman, 2010; Sellin et al, 2014). It is possible that posterior brain regions are particularly affected.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in the literature have addressed this specific entity and have come up with specific conclusions. Sellin et al 19 observed that patients with hydrocephalus initially presenting with ventricular dilation subsequently presented with dilated ventricles in cases of shunt malfunction. Similarly, nondilation at the initial presentation made subsequent presentation with dilated ventricles less likely in cases of shunt obstruction.…”
Section: Discussionmentioning
confidence: 99%